Women’s attitudes towards discontinuation of female genital mutilation in Egypt - Dalal, Koustuv; Lawoko, Stephen; Jansson, Bjarne (Journal of injury and violence research, 2010)
To examine women’s attitude towards discontinuation of female genital mutilation (FGM) in association with their access to information, knowledge of health effects and cultural beliefs concerning FGM in Egypt. Methods: A cross-sectional study of 9159 women, using data from the household survey in Egypt by Demographic and Health survey 2003. A comprehensive questionnaire covering attitudes towards FGM, demographics, and access to information was used. Chi-square analysis and logistic regression were applied to investigate how demographics, level of education, access to information, knowledge of health consequences and cultural beliefs influence women’s attitudes towards FGM. Results: Among the demographic variables, discontinuation of FGM was independently associated with urban residency and post-secondary education. Moreover, women who were informed by the media, and those who had attended community meetings, church, or mosque where FGM was discussed, as well as women who were aware of the negative health consequences of FGM, were more likely to support discontinuation of FGM. By contrast, women with positive cultural conceptions of FGM were less likely to favor its discontinuation. Conclusions: Public education and information dissemination aiming to change current cultural notions favoring FGM practice – through community and religious leaders, and radio and television programs – may play an important role in modifying women’s attitudes towards FGM. These findings have some implications for intervention and policy.
Keywords: Female genital mutilation; Attitude; Violence against women; Egypt